Emergent electrostatics in planar XY spin models: the bridge connecting topological order with broken U(1) symmetry - Michael F Faulkner (New Journal of Physics)
Topological phases have been a central focus of condensed-matter physics for over 50 years. Along with many experimental applications, they have provided much intellectual interest due to their characterization via some form of topological ordering, as opposed to the symmetry-breaking ordering of conventional continuous phase transitions. This distinction is most subtle in the case of the Berezinskii–Kosterlitz–Thouless (BKT) transition as its experimental realizations appear to break U (1) symmetry at low temperature. It also presents two further paradoxes: (i) its prototypical short-range interacting planar XY spin model behaves as an emergent long-range interacting electrolyte; (ii) its topological ordering is not accompanied by a topological nonergodicity within the BKT picture. This review paper addresses these three interconnected questions. We review a series of papers that demonstrate that U (1) symmetry is indeed broken, but within a broader framework than that traditionally used to characterize broken symmetry. We discuss recovery of this symmetry by breaking velocity-symmetry in a deterministic Markov process. We then expand on a modern field theory of the emergent electrolyte that maps directly from the spin field to an emergent lattice electric field governed by an augmented electrostatic Boltzmann distribution. This local model of electrolyte physics resolves both the short-range–long-range paradox and the question of topological nonergodicity—as in contrast with the BKT picture, it describes global topological defects and their nonergodic freezing by the topological ordering. It also connects the broken U (1) symmetry with the topological ordering, providing a comprehensive framework for broken symmetry at the transition. We introduce long-time topological stability as a measure of topological nonergodicity—within a general framework for weakly broken ergodicity.